Togo : 2007 Article IV Consultation and First Staff Review of the Staff-Monitored Program; Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Togo. (IMF Staff Country Reports; Country Report, 2007)
The 2007 Article IV Consultation highlights Togo's developments and performance under the Staff-Monitored Program (SMP). Togolese banks have the highest nonperforming loan (NPL) ratio in the West African Economic and Monetary Union (WAEMU) area, reflecting primarily past lending to loss-making enterprises in the cotton and phosphate sectors. Executive Directors commended the progress made in restoring fiscal discipline and strengthening governance, in particular the reforms to strengthen tax and customs administration and improve expenditure control.